Zur Kriminal- und Strafrechtspolitik des 21. Jahrhunderts. Der Blickwinkel eines nordischen Wohlfahrtsstaates und dessen Strafgesetzreformen: Finnland - Lahti, Raimo (Strafrechtswissenschaft und Strafrechtspolitik, 2019)
The volume brings together 18 articles published by the author between 1985 and 2017. These focus on the reforms to Finland's Criminal Code, which were concluded in 2003 following a process lasting over 30 years. Further articles offer an insight into developments in criminal law in Scandinavia more broadly.